A heterozygous mutation in NOTCH3 in a Chinese family with CADASIL - Li, Juyi; Luo, Tao; Wang, Xiufang; Wang, Mengjie; Zheng, Tao; Dang, Xiao; Deng, Aiping; Zhang, Youzhi; Ding, Sheng; Jing, Ping; Zhu, Lin (Frontiers in Genetics, 2022)
Introduction: Cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an autosomal dominant systemic vascular disease that primarily involves small arteries. Patients with CADASIL experience migraines, recurrent ischemic strokes, cognitive decline, and dementia. The NOTCH3 gene, which is located on chromosome 19p13.12, is one of the disease-causing gene in CADASIL. Herein, we investigate the genetic and phenotypic features in a Chinese CADASIL family with heterozygous NOTCH3 mutation. Methods and Results: In the family, the proband suffered from dizziness, stroke and cognitive deficits. Brain magnetic resonance imaging (MRI) demonstrated symmetrical white matter lesions in the temporal lobe, outer capsule, lateral ventricle and deep brain. Whole exome sequencing identified a known missense mutation in the proband, c.397C>T (p.Arg133Cys), which was identified in his son and granddaughter using Sanger sequencing. The proband’s younger brother and younger sister also have a history of cognitive impairment or cerebral infarction, but do not have this genetic mutation, may highlight the impact of lifestyle on neurological disease. Conclusions: We identified a known CADASIL-causing mutation NOTCH3 (c.397C>T, p.Arg133Cys) in a Chinese family. The clinical manifestations of mutation carriers in this family are highly heterogeneous, which is likely a common feature for the etiology of different mutations in CADASIL. Molecular genetic analyses are critical for accurate diagnosis, as well as the provision of genetic counseling for CADASIL.